Posterior Tibial Slope in Patients Undergoing Anterior Cruciate Ligament Reconstruction With Patellar Tendon Autograft: Analysis of Subsequent ACL Graft Tear or Contralateral ACL Tear. Issue 3 (March 2021) - Shelbourne, K. Donald; Benner, Rodney W.; Jones, Jonathan A.; Gray, Tinker
Background: Reports on greater posterior tibial slope (PTS) and its relationship to subsequent anterior cruciate ligament (ACL) injury show conflicting results; it has not been studied much in patients after ACL reconstruction with patellar tendon autograft (PTG). Hypothesis: Patients who suffered a subsequent ACL injury would have a larger PTS than patients who did not suffer a subsequent injury after primary or revision ACL reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Patients received primary (n = 2439) or revision (n = 324) ACL reconstruction with PTG and were followed prospectively to determine the rate of graft tear and contralateral ACL tear. The PTS was measured preoperatively on digital lateral view radiographs. Intersecting lines were drawn along the medial tibial plateau and posterior tibia; the value of the acute angle at the lines' intersection was then subtracted from 90° to obtain the PTS. This procedure was completed by a clinical assistant with an intrarater reliability of 0.89. Chi-square analysis and t tests were used to determine the differences between rate of tears and measurements between groups. A threshold of PTS ≥10° was used for analysis. Results: The mean follow-up time was 11.6 ± 4.0 years. After primary surgery, the mean PTS in patients with graft tears was 5.4°± 3.1° versus 4.8°± 2.9° for patients without a tear ( P = .041). The mean PTS was 4.9°± 3.4° for patients with contralateral tears (not statistically significantly different than the no-tear group; P = .80). Furthermore, patients with primary reconstruction with PTS ≥10° had a statistically significantly higher rate of graft tear (9.7%) than patients with PTS ≤9° (4.8%) ( P = .003), but not a higher rate of contralateral tear. Among patients undergoing revision surgery, there were no statistically significant differences between the graft tear, contralateral tear, and no-tear groups with relation to PTS ≥10°. Conclusion: After primary ACL reconstruction, patients with PTS >10° had a higher rate of subsequent graft tear but not a higher rate of contralateral tear. With revision surgery, there was no significant association between PTS and the rate of subsequent tear. Therefore, caution should be exercised when considering more radical interventions, such as osteotomy, to prevent retear in patients with high PTS.